The Ambivalence In Hisaye Yamamoto’s Seventeen Syllables - Trisnawati, Ai; Wiranti, Ida; Faujiah, Neuis Nurul; Amindari, Seftiani; Wartini, Titin (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to reveal the ambivalence in the short story Seventeen Syllables (1988) by Hisaye Yamamoto. This study uses qualitative methods. "Seventeen Syllables" was written by Japanese-American author Yamamoto, who focused on the various problems faced by Japanese immigrants to the United States in the late 19th century. She writes stories that capture the disconnect between her original Japanese family and her children exposed to American culture. The ambivalent issue in this short story is illustrated by the main characters, namely Rosie, who is pro-American, and her mother, who faces a cultural gap between Japanese and American culture, which then relates to the relationship between parents and children. This short story shows how differences in culture and values will cause tension and disputes, especially between different generations in an immigrant family, which will put the family in the middle between the original culture and the new culture. With characters representing different cultures and generations, Yamamoto creates interesting stories and complex games. She showed that Japanese Americans still struggle with ambivalence about their cultural identity and the balance of different cultures and values in their lives in America. The stories in Seventeen Syllables represent the voices of marginalized minorities and celebrate the complex struggles for cultural identity in America's multicultural society. This intergenerational conflict often creates ambivalence and confusion, especially when the original and new cultures overlap. With the aim of the issue of ambivalence, this study uses post-colonial theory, which is narrowed down by Homi's theory. K Bhabha which includes the concepts of ambivalence, mimicry, and hybridity.